(untitled) (LEARNing Landscapes, 2010)
I draw on poetic inquiry to explore my experience using and interpreting haiku within the context of a literacy methods course. From this project I learned that poetry, as a pedagogical tool as well as one of inquiry, opens up spaces for (un)imaginable possibilities to be exposed, moving both teacher and students toward a place of praxis and reflexive agency